Association of atopic dermatitis and headache disorder: a systematic review and meta-analyses - Yang, Wei; Dai, Hong; Xu, Xiao-feng; Jiang, Hai-yin; Ding, Ji-yuan (Frontiers in Neurology, 2024)
Background Growing evidence suggests that headache disorders and atopic dermatitis share similar pathological mechanisms and risk factors. The aim of this study was to assess the risk for headache disorders in patients with atopic dermatitis. Methods We systematically searched the PubMed and Embase databases from inception to December 1, 2023, for observational studies that examined risk of migraine in subjects with atopic dermatitis. Risk estimates from individual studies were pooled using random-effects models. Results Ten studies with 12,717,747 subjects were included in the meta-analysis. Our results showed that patients with atopic dermatitis were associated with a higher risk of headache disorder (OR, 1.46, 95% CI = 1.36–1.56; P < 0.001; I2 = 98%) or migraine (OR, 1.32, 95% CI = 1.18–1.47; P < 0.001; I2 = 98.9%). Most of the results of the subgroup analyses were consistent with the overall results. Conclusion The findings of this meta-analysis suggest that atopic dermatitis is a potential risk indicator for headache disorder or migraine. Further studies are still needed to verify our findings due to the substantial heterogeneity in our analyses.